DEVELOPMENT OF “INTELLIGENT RULER” TO ENHANCE MEASUREMENT SKILLS OF SPECIAL EDUCATION NEEDS (SEN) STUDENTS IN THE SUBJECT OF SPECIFIC VOCATIONAL SKILLS: BASIC CLOTHING SEWING (Proceedings of International Conference on Special Education, 2025)
Skills in TVET (Technical and Vocational Education and Training) are an important aspect that needs to be instilled among students, especially for Special Education Needs (SEN) students. This skill requirement serves as an early preparation for SEN students to be involved actively and effectively in the industry upon completing their education. Therefore, one of the subjects that apply hands-on skills for SEN students is the subject of Basic Clothing Sewing, which involves fundamental technical tasks such as accurate measurement. Therefore, this study aims to identify the level of measurement skills among SEN students and the need for the development of Teaching Aids, namely "Intelligent Ruler". The study population was centered at Sekolah Menengah Kebangsaan Bandar Seri Putra. The sample of this study was focused on 20 SEN students who took the subject of Basic Clothing Sewing and 10 teachers who were directly involved in teaching SEN students. The data obtained from the teacher's feedback found that the skill level of the SEN students face serious challenges in measurement related skills. A total of 34% of students were categorized as “Very Weak”, while 33% were at the “Weak” level. Meanwhile, the assessment of students' assignments is according to the range of the Sijil Pelajaran Malaysia (SPM) examination which is at grade G which is the lowest. Therefore, 100% of teachers also agree if this “Intelligent Ruler” is developed. In conclusion, the development of the “Intelligent Ruler” is very much needed and seen as a practical solution to help improve the level of measurement skills among SEN students, thereby increasing their mastery, confidence, and future employability in TVET-related fields.